Surgical Correction of Mandibular Prognathism - Brigadier Rasamay Ganguly; Capt. S. C. Anand (Indian Journal of Plastic Surgery)
1. The underlying skeletal defect and dental malocclusion in mandibular prognathism have been analysed.